Indonesia’s Maritime Axis and the Security of Sea Lanes of Communications (SLOCs) in the Indo-Pacific - I Gusti Bagus Dharma Agastia; Anak Agung Banyu Perwita (Jurnal Hubungan Internasional, 2016)
This article tries to elaborate the strategic position of Indo-Pacific in the current international relations. This region has become a new crucial theatre for the global sea lanes of communication. As a littoral country in the Indo-Pacific, Indonesia relies heavily on the SLOCs in the Indo-Pacific. Indonesia, as a developing economy, requires a steady supply in oil and gas from the Gulf. A sudden disturbance in oil resources would have a catastrophic effect on energy security in Indonesia, which could lead to other security implications. Indonesia has mostly been active in safeguarding the Malacca Strait, one vital SLOC in the Indo-Pacific. This article also elaborates President Jokowi’s maritime axis as a guarantor of maritime security not only in Southeast Asia, but the entire Indo-Pacific.